Decision Support System for Determining Vaccination Priorities Using the AHP TOPSIS Method - Rachmat Agusli; M. Ramaddan Julianti; Ardi Ahmad Winata (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
Vaccination is the administration of vaccines to a living being to stimulate the formation of an immune system against a virus, while mass vaccination is the simultaneous administration of vaccines to a group in the form of organizations, companies, or the wider community to create herd immunity. However, with the limited number of vaccines available, it is not possible to carry out a thorough vaccination of a group with a very large number of members. It requires determining in advance who will be prioritized for the vaccine. The purpose of this study is to build a system that can automatically determine vaccination priorities to be more effective and efficient by implementing a decision support system using the Analytical Hierarchy Process (AHP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The result of this study is the formation of a Web-based decision support system application that produces the output of alternative ranking sequences as objects that will be prioritized for vaccines based on calculations against predetermined criteria.